„I razem sobie zmyślamy różne bajeczki i bzdurki”. Lingwizm w poezji Danuty Wawiłow - Kwiatkowska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Danuta Wawiłow’s poems for children were created in the second half of the 20th century. The poems classify as the language poetry, employing in the compositions the mechanisms and figures of speech characteristic of this aesthetic current. The poet uses stylization, she reconstructs the creative attitude to language typical of kindergarteners, which is based on experimentation and abounding in similar-sounding words. Wawiłow implements the particularly strongly individualized variation of linguism. She tests the language potential with regards to the needs of an individual – a child who attempts to express their feelings, thoughts, and emotions. Wawiłow’s poetry is not only focused on the language, but also explores the subjectivism of the lyrical subject and new ways of its expression.